Practical hazops, trips and alarms - Macdonald, Dave, 1942- (Amsterdam ; Boston : Newnes/Elsevier, 2004)
Do you have trips and safety interlocks in your plant? Are they good enough or are they perhaps over-designed and much more expensive than necessary? Are you or your company aware of how Hazard Studies should define risk reduction requirements? Are you actually using Hazard Studies at all? The answer is the integrated approach to safety management. New international standards combined with well-proven hazard study methods can improve safety management in your company. Practical Hazops, Trips and Alarms for Engineers and Technicians describes the role of hazard studies in risk management, and then proceeds with basic training in Hazop techniques. A number of practical exercises support the reference information and allow you to test your understanding of the material in the book. This book aims to bridge the discipline gap between hazard studies and the provision of safety-related alarm and trip systems. It provides training in hazard and operability methods (Hazops) and in the principles of safety instrumented systems as defined by international standard IEC 61508. 1. Design an integrated safety management system to increase efficiency and reduce costs 2. Learn how to carry out hazard and operability studies (Hazops) and find out how to convert Hazop outputs into safety requirements specifications 3. Implement safety instrumented systems to the new IEC standards (IEC61508).
Hazard studies at levels 1 & 2 -- Risk reduction measures using alarms and trips -- Hazop method -- Planning and leadership of Hazops -- Specifying safety instrumented systems -- Hazard analysis methods -- Factors in the choice of protection system -- Exercise in specifying an SIS from the Hazop.
Includes index.
Keywords: Industrial safety; Manufacturing processes -- Safety measures; Risk management; Risk assessment; Electronic books